Role-Playing Methods: Efforts to Stimulate the Development of Early Childhood Numeracy Literacy - Ismatul Khasanah; Iin Purnamasari (International Journal Labs, 2023)
The development of early childhood numeracy literacy in the form of the ability to apply the concept of numbers and counting operation skills in everyday life needs to be stimulated by various methods, one of which is role-playing. This research aims to determine efforts that can stimulate the development of early childhood numeracy literacy with role-playing methods. The data collection technique in this research uses literature studies by exploring journals relevant to the study. The results showed that role-playing efforts have a pattern in their implementation that is adapted to goals that demand a certain form of participation. Efforts to stimulate children's numeracy literacy can be by buying and selling fruits in a market, children will play based on their respective roles, namely as sellers and buyers and children demonstrate both language, numeracy and behavior like these characters in real life.